2005
DOI: 10.1063/1.1999008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative copper measurement in oxidized p-type silicon wafers using microwave photoconductivity decay

Abstract: Iron detection in polished and epitaxial silicon wafers using generation lifetime measurements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…the lifetime/diffusion length variation before and after light soaking) has been correlated to quantitative measurements of the interstitial Cu concentrations involved in the degradation process. 23,24 After transforming the measured diffusion lengths into the corresponding lifetimes and inserting the obtained lifetime values into the empirical formula proposed in Ref. 24, we find an average Cu concentration of ∼7 × 10 13 cm 3 in the reference samples with no emitter, which approximately corresponds to the Cu contamination levels reported by several authors in as-cut solar-grade wafers.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…the lifetime/diffusion length variation before and after light soaking) has been correlated to quantitative measurements of the interstitial Cu concentrations involved in the degradation process. 23,24 After transforming the measured diffusion lengths into the corresponding lifetimes and inserting the obtained lifetime values into the empirical formula proposed in Ref. 24, we find an average Cu concentration of ∼7 × 10 13 cm 3 in the reference samples with no emitter, which approximately corresponds to the Cu contamination levels reported by several authors in as-cut solar-grade wafers.…”
Section: Resultsmentioning
confidence: 54%
“…23,24 After transforming the measured diffusion lengths into the corresponding lifetimes and inserting the obtained lifetime values into the empirical formula proposed in Ref. 24, we find an average Cu concentration of ∼7 × 10 13 cm 3 in the reference samples with no emitter, which approximately corresponds to the Cu contamination levels reported by several authors in as-cut solar-grade wafers. 1,12,25 In Group A, the residual Cu concentration after gettering is estimated to be ∼3.8 ×10 13 cm 3 (i.e.…”
Section: Resultsmentioning
confidence: 54%
“…In Cz samples with intentionally grown oxygen precipitates, Cu-LID has been shown to exhibit degradation behavior that can be interpreted to be characteristic of heterogeneous nucleation. 19 This means that the degradation rate of Cu-LID increased and final lifetime decreased considerably when the density of nucleation sites provided by the oxide precipitates was increased. On the other hand, Cu-LID derived from homogeneous precipitation was speculated to occur in wafers that did not undergo the intentional nucleation site creation stage.…”
mentioning
confidence: 99%
“…11,12 In p-type Si, provided that the Cu contamination level is below the doping level, excess carrier injection (through, e.g., illumination) is necessary to activate lifetime degradation. 11,[13][14][15][16][17][18][19][20] For these reasons, Cu-related lightinduced degradation (Cu-LID) is only observed in p-type Si. Owing to the fundamental difference in defect activation between n-and p-type Si, especially early contributions 11,13 attributed Cu-LID in p-type Si to a different defect than precipitates, and ambiguity has existed ever since.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic optical absorption in single crystal germanium (Ge) and Si was studied 4 at the temperatures 77 and 300K, the threshold for direct transition was found to be at 2.5 eV and that for indirect transitions were at 1.06 eV and 1.16 eV at 300 and 77K, respectively. Microwave Photoconductive decay (µ-PCD) was used 5 to find out the copper (Cu) contamination in p-type Si and it was found that the method was capable of measuring Cu concentrations down to 10 10 /cm 3 . The optical parameters and the thickness of Si: H thin films were determined 6 from transmission spectrum in the range of 400-2500 nm using the envelope method and detailed analysis was carried out to obtain the optical band gap (E g ) using Tauc's method and the estimated values were 1.99 eV, 2.01eV and 1.75 eV.…”
Section: Introductionmentioning
confidence: 99%